2016
DOI: 10.1111/peps.12184
|View full text |Cite
|
Sign up to set email alerts
|

Dropped on the way to the top: Gender and managerial derailment

Abstract: We attempt to make sense of ongoing gender disparities in the upper ranks of organizations by examining gender bias in leaders’ assessments of managers’ derailment potential. In a large managerial sample (Study 1: N ∼ 12,500), we found that ineffective interpersonal behaviors were slightly less frequent among female managers but slightly more damaging to women than men when present. Evidence of bias was not found in performance evaluations but emerged when leaders were asked about derailment potential in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 85 publications
1
42
0
Order By: Relevance
“…The present results indicate no differences between men and women concerning their management skills, although women being more empathetic than men. The first finding is consistent with extant research that did not relate gender differences to the capacity to exercise individual management competencies (Bono et al , ; Gorbacheva, Stein, Schmiedel & Müller, ; Trauth, ). In this sense, managers and leaders, whether men or women, should have a set of skills to ensure an accurate execution of their jobs, namely empathy and sensitivity, as well as moral solidarity, commitment, and concern, especially during or after crises (Ciulla, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present results indicate no differences between men and women concerning their management skills, although women being more empathetic than men. The first finding is consistent with extant research that did not relate gender differences to the capacity to exercise individual management competencies (Bono et al , ; Gorbacheva, Stein, Schmiedel & Müller, ; Trauth, ). In this sense, managers and leaders, whether men or women, should have a set of skills to ensure an accurate execution of their jobs, namely empathy and sensitivity, as well as moral solidarity, commitment, and concern, especially during or after crises (Ciulla, ).…”
Section: Discussionsupporting
confidence: 86%
“…Regarding individual management competencies, the literature does not relate gender differences to the capacity to exercise individual competencies, since the degree of complexity of the attributes and responsibilities of male and female leaders be equivalent (Bono, Braddy, Liu et al , 2). The literature also shows that it seems consensual that men and women are more identical than distinct in terms of traits and management skills (Gorbacheva, Stein, Schmiedel & Müller, ; Trauth, ).…”
Section: Introductionmentioning
confidence: 99%
“…The logic of this framework reflects recent research on gender bias and discrimination, which contends that men and women are treated differently even when they bring similar behavior, circumstances, or attributes into their careers (e.g., Bono et al, 2016;Inesi & Cable, 2015;Koch, D'Mello, & Sackett, 2015;and Motro & Ellis, 2017). The unequal effects framework thus accommodates both overt discrimination and unintentional bias-such as unknowingly lying to female negotiators more often than male negotiators (Kray, Kennedy, & Van Zant, 2014)-making it broader in scope than the views commonly expressed in popular discourse and in former theories of discrimination (i.e., statistical and taste-based discrimination ;Aigner & Cain, 1977;Becker, 1957).…”
Section: Unequal Effects Frameworkmentioning
confidence: 98%
“…For example, a recent large-scale study has shown that engaging in ineffective interpersonal behaviors, which is strongly related to gender stereotyping about communality (i.e., women are perceived warmer and kinder than men), is more damaging for female leaders than for male leaders, despite these leaders having similar performance evaluations (Bono et al, 2016).…”
Section: Biological Sex Gender and Leadershipmentioning
confidence: 99%